The method for studying temperature deformations of self-lubricating bearing friction units of high-temperature low-flow turbine - N. A. Raykovskiy; V. L. Yusha; A. V. Tretyakov; V. A. Zakharov; K. I. Kuznetsov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
In the paper proposes a method for the numerical study of temperature deformations of cooled self-lubricating turbo-compressor bearings, the cooling system of which is implemented by the «water jacket» type based on the ANSYS CFX. Approbation of the method is implemented on the example of a low-flow turbine unit with a console arrangement of two bearing units. The method of engineering analysis in terms of temperature deformations, taking into account the temperature field corresponding to the actual operating conditions, provides an acceptable deviation in the calculation results